Socio-demographic determinants influencing antenatal care seeking behaviour among women in Bangladesh: an application of factor analysis - Jahan, Mosrat; Jahan, Esrat (International Journal Of Community Medicine And Public Health, 2017)
Background: Pregnancy-related complications are one of the leading causes of death among women in the reproductive ages in developing countries. Antenatal care is an essential component for reducing maternal and infant morbidity and mortality. The study had been made an attempt to investigate the socio-demographic determinants of antenatal care seeking behavior among women in Bangladesh. Methods:Present study used secondary data from Bangladesh Demographic and Health Survey (BDHS-2011) with married women aged between 15-49 years. Results were obtained by adopting data reduction procedure and multinomial logistic regression model. Results: Factor analysis procedure had been used to determine two factors: (F1) “current status of age & reproductive experience” - consisted of the variables respondent’s age, partner’s age, marital duration, and number of living children; and (F2) “initial status of marital age & birth” - consisted of the variables age at marriage and age at 1st birth. These two factors were used in the subsequent analysis instead of the six demographic variables. The logistic regression analysis indicated region, type of place of residence, education, wealth index, Mass media exposure and two extracted factors had significant influence on antenatal care seeking behavior in Bangladesh. Conclusions:This study suggests that cultural issues, demographic and socioeconomic status are important determinants of Antenatal care seeking behaviour. Appropriate programs for strengthening female education and women empowerment should be to improve the health of mothers and children in the country.